DISPUTES RESOLUTION OF WORK TERMINATION ON INDUSTRIAL RELATIONS THROUGH MEDIATION DURING THE COVID-19 - Nurani, Nina; Silaen, Abner; Apianti, Pepi (CENTRAL ASIA AND THE CAUCASUS, 2022)
Companies efforts dealing with employment termination (PHK) in order to reduce losses due to the Covid-19 condition by the consideration of force majeure have caused conflicts between various parties, especially for the matter resulting in industrial relations disputes. In order to handle the disputes intensively and professionally, a third party is required as a mediator in solving the disputes through solutions. Furthermore, mediators must deal with various challenges when it happens. This study purposes to find out how to resolve disputes in industrial relations due to work termination by mediation during Covid-19. This study applies qualitative descriptive method. In addition, the literature study for this research generates data collection techniques. The results of the study show that the policy of massive work termination by companies with consideration of force majeure during the Covid-19 has created various conflicts that require more comprehensive criteria. The role of the mediator is not optimal due to various obstacles, as the employers and workers do not understand the labor regulations comprehensively, the employer and the workers have limited time to attend the trial, the technical delivery of letters has not been effective and the number of mediator human resources is still minimal. A reorientation of the contents of work agreements, company regulations and CLAs are highly required in addition to the need of administrative information technology transfer.